Thyroid Transcription Factor-1 Activity is Required for the Proliferation of Human Thyroid Cancer Cells 8505C - Christophe-Hobertus, Christiane; Lefort, Anne; Libert, Frederick; Christophe, Daniel (Journal of Thyroid Cancer, 2016)
Thyroid transcription factor-1 (TTF-1) is known to play key roles in thyroid organogenesis, in thyroid cell proliferation and in the expression of genes involved in thyroid differentiated function. Many human thyroid cancer cell lines keep producing TTF-1 despite the loss of differentiated gene expression, raising a question about the role of the factor in these cells. In order to investigate this point, we used a chimeric protein acting as a functional antagonist of TTF-1 transcriptional activity that was expressed conditionally in 8505C cells originating from an anaplastic thyroid carcinoma. We observed a growth arrest of 8505C thyroid cancer cells when the endogenous TTF-1 transcriptional activity was inhibited. It correlated with decreased levels of several mRNAs encoding positive effectors of cell proliferation like CDK1 and cyclinB1, and increased levels of various mRNAs encoding negative regulators of cell division like CDKN2B and DUSP6. In conclusion, the persistence of TTF-1 expression observed in the dedifferentiated human thyroid cancer cell line 8505C reflects the need of TTF-1 activity for the proliferation of these tumor cells.
Keywords: thyroid; cancer; TTF-1; gene expression; cell proliferation.